3√2+2√3/3√2-2√3 = a+b√6
Answers
Answered by
7
Answer:
First we multiply the numerator & denominator by (3√2+2√3) then we use formula in the denominator = a+b)(a-b) = a^2-b&2
-----------------------------------------------------------------------------------------------
The value of a= 2 & b= -5/6
----------------------------------------------------------------------------------------------
hope this will help you...
Step-by-step explanation:
I hope this helps you plz make me branly
Attachments:
![](https://hi-static.z-dn.net/files/daf/1daa278621ddff91fa27076c4c3a83a2.jpg)
Similar questions